Penerapan Periodic Review System Untuk Pengelolaan Bahan Baku Produksi Bebek Panggang Di Umkm Papa Zen - Faesal Hermawan; Widya Setiafindari (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
Pawon Papa Zen MSME faces raw material inventory control problems because ordering is still based on estimates, resulting in excess inventory and high inventory costs. This study aims to develop an inventory control policy using the Periodic Review System method to optimize raw material inventory costs. A quantitative approach was employed using raw material usage and ordering data from January to December 2025. The results showed that the existing inventory cost was Rp6,558,763 per year, while the implementation of the Periodic Review System reduced the inventory cost to Rp2,263,530 per year. The proposed method generated cost savings of Rp4,295,233 or 65.49%. Therefore, the Periodic Review System can be used as an effective alternative to improve the efficiency of raw material inventory control at Pawon Papa Zen UMKM.